If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15c + 90 = -90 Reorder the terms: 90 + 15c = -90 Solving 90 + 15c = -90 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 15c = -90 + -90 Combine like terms: 90 + -90 = 0 0 + 15c = -90 + -90 15c = -90 + -90 Combine like terms: -90 + -90 = -180 15c = -180 Divide each side by '15'. c = -12 Simplifying c = -12
| z+0.2z+0.6=6(z-6.3) | | A-7+3-4a=-4-3a | | 3.5x-4=3 | | 14x^2+4+3x-12x^2-3+11x= | | (x+5)2-529=0 | | 4x-7=9x+6 | | (3y-x)(2x+y)= | | Cot*4x=-1 | | 4(3+y)= | | 9(1+x)= | | 5n-45= | | y=[x+(1+2i)][x+(1-2i)] | | 4b+64= | | 7(k-6)= | | x-8/5=6 | | y/3-6=10 | | 6x(x+y)+7(x+y)= | | 6x^3+4x^2-42x=0 | | 9x+y=-68 | | 2x-4y=26 | | y=x^4-6x^3+11x^2-6x+1 | | 96=160+-16t^2 | | 32.41xX=25 | | 32.41=25xX | | 3x+2iy=-6x-3i | | 40-3/4= | | 6v=-54 | | 3x+0=45 | | 6y^2-y-9=0 | | 50+5x=20+6x | | x^2dy=(xy+y^2)dx | | 7q^28= |